25 Years' Experience with Redo Operations in Cardiac Surgery—Third-Time Sternotomy Procedures - Rupprecht, Leopold; Schopka, Simon; Keyser, Andreas; Lunz, Dirk; Sossalla, Samuel; Hilker, Michael; Schmid, Christof (The Thoracic and Cardiovascular Surgeon, 2020)
Background Over the years, open heart surgery has become more complex, and especially reoperative surgery, more demanding. The risk of third-time or more sternotomy procedures is unclear.Methods We reviewed our institutional experience of 25 years based on two generations of cardiac surgeons in a German university medical center to document frequency, outcome, and complications of the various types of open heart procedures.Results Overall, we included 104 patients with a mean age of 64 ± 13 years. The EuroSCORE II (European System for Cardiac Operative Risk Evaluation) calculated an average mortality risk of 15.7 ± 15.4%. Subgroup comparison of isolated coronary artery bypass grafting (CABG), aortic valve replacement, and mitral valve replacement procedures did not delineate significantly different risk profiles except for the incidence of acute myocardial infarction, which was present in every second patient (53.3%) scheduled for CABG surgery. The time interval to previous surgery was 4.7 ± 6.3 years on average. Most frequent surgical procedures were valve operations, which were accomplished in 72 patients (69.2%), whereas coronary bypass surgery was performed in 23 patients (22.1%) only. Combined procedures were performed in 27 patients. Complex aortic arch replacement with a frozen elephant trunk procedure was necessary in six patients. Overall, 30-day survival was 81.7%.Conclusion In conclusion, third-time and more sternotomy procedures offer acceptable outcome and should therefore be considered in appropriate patients.
Keywords: aortic valve or complete root; coronary artery bypass grafting; CABG; aortic valve surgery; reoperation